Pengaruh Personal Branding dan Service Desired terhadap Customer Retention Gojek di Pasuruan - Jilan Zenikasari; Yufenti Oktafiah; Dwita Laksmita Rachmawati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The development of application-based digital services, such as Gojek, requires service providers to focus not only on efficiency but also on the quality of interactions between partners and users. In the context of increasingly fierce competition, customer retention is crucial. One factor that can influence user loyalty is how partners build their self-image (personal branding) and the extent to which the services provided meet customer expectations (service desires). This study aims to determine the effect of personal branding and service desires on customer retention among Gojek service users in Pasuruan City. This study used a quantitative approach with a survey method. A sample of 70 respondents was selected using a purposive sampling technique. Data were collected through a questionnaire and analyzed using multiple linear regression.  The partial test results (t-test) show that personal branding has a significant effect on customer retention with a calculated t value of 5.339 ttable 1.667 and a significance of 0.000 <0.05. Service desired also has a significant effect on customer retention with a calculated t value of 5.050> ttable 1.667 and a significance of 0.000 <0.05. The simultaneous test (F test) shows a calculated F value of 19.970> Ftable 3.13 and a significance of 0.000 <0.05, which means that both variables together have a significant effect on customer retention. The coefficient of determination (R2) value of 0.373 indicates that 37.3% of the customer retention variable is influenced by personal branding and service desired, while the rest is influenced by other factors outside the study.  These findings demonstrate the importance of building a strong personal brand and meeting customer expectations in increasing user loyalty to digital services like Gojek.